(untitled) (Research, Society and Development, 2023)
The liver is an indispensable organ for maintaining our body’s homeostasis, being responsible for important functions such as the elimination of toxins. It has a considerable capacity for regeneration, however, when these aggressions do not cease, regeneration occurs incorrectly, resulting in scars and nodules. Given the epidemiological importance of HE, this article aims to discuss the pathophysiological mechanisms of the disease. This study is a narrative review with the purpose of discussing and describing HS and its pathophysiology, as well as demonstrating how this syndrome affects the personal lives of affected individuals. The following databases were used: SciElo (Scientific Electronic Library Online) and PubMed (US National Library of Medicine), with scientific data from January 2, 2023, with no language restriction and no restriction on the year of publication. Several studies show that the major neuroinhibitory system, GABA, is increased in HE. Furthermore, an important consideration for ammonia in the face of the syndrome must be exposed; the receptors that are located on the periphery of the mitochondria, due to the presence of ammonia, as well as ligandins, triggering the activation of neurosteroid production in astrocytes. In any case, all studies have stated that the later the diagnosis is made, the more severe the systemic consequences of the pathology will be. In addition, it is of fundamental importance that the medical centers responsible for offering hospital support to patients affected by HE are prepared.